Penerapan Metode Bercerita untuk Meningkatkan Konsentrasi Belajar Anak Kelompok B3 TK IT Salsabila Al-Muthi’in Banguntapan, Bantul - Pitaloka, Gyasya (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2019)
A learning disability can came upon a child. A learning disability can affect many aspects of life, one of them is in school. one of learning disability children is not concentrate while learning held. Every child has their own level of focus and concentration. The same thing happened to children in a group B3 at TK IT Salsabila Al-Muthi’in in less of concentration when the learning goes on. The purposes of this research are: (1) to find out the extent to which unsolved of concentration of children learning, (2) figure out how to the application of a method of confided in increase the concetration of children learning, and (3) know how much an increase in the concentration learn the value of child after enactmen of a method of storytelling. The type of this research is Classroom Action Research conducted in 2 cycle holding the observation, interview and documentation. The research include: planning, fostering, observation and reflection. The result showed that: (1) before did the act of only 15,78% or three children at criteria developed as expected, (2) the act of fostering as many as two cycle and every cycle there are three meetings, (3) increase after the actions that can be seen in the first cycle is 47,38% develops in accordance the criteria developed as expected and for the second cycle that reveals 89,49% childrem divided into 57,91% reached criteria developed as expected and 31,58% reached criteria developing very well.